Captan utilization by a soil bacterium Planomicrobium flavidum strain EF - Mohamed, Eman; Abd El-Motaleb Mostafa, Fatma (Penerbit Universiti Kebangsaan Malaysia, 2018)
The fungicide captan, which is commonly used to control fungal diseases in many plants, causes soil infertility and cancer to human beings. Hence, this fungicide was tested for utilization as a sole carbon source by a newly soil isolate, Planomicrobium flavidum strain EF. This bacterium resists captan up to 2000 ppm and showed higher growth patterns in minimum salt medium supplemented with captan only, if compared with minimum salt medium without captan. Moreover, almost 77.5% of captan has been utilized by Planomicrobiu flavidum after only 2 h of growth under shaking conditions and only 0.8% of the fungicide was remained after 24 h of bacterial growth. Captan residues in both soil samples and minimal salt medium were accurately estimated using GC-ECD (gas chromatography - electron detector) and GC-MS/MS (gas chromatography - mass spectrum) technologies. According to current results, Planomicrobium flavidum strain EF is highly recommended for captan and may be other fungicides bioremediation.